Pendampingan Terhadap Siswa Melalui Kelas Inspirasi di SDN 7 Jeumpa Kabupaten Aceh Barat Daya - Anhar Fazri; Al Munawir Al Munawir; Putri Kemala Sari; Sri Wahyu Handayani; Zuhrizal Fadhly; Alimas Jonsa (Universitas Teuku Umar, 2020)
Education is an effort to channel knowledge from educators to students through a tiered process. Elementary school students are students at the next level who must obtain extraordinary motivation to support the dream process they have, especially for students at SDN 7 Jeumpa, Aceh Barat Daya District. That way, creating an inspiring class that can give an idea of their dreams in the future will be a form of motivation that is able to push them toward a better future. The method used in this service is by lecturing, sharing sessions, and direct practice in accordance with the profession. The results of the dedication show that very many students at SDN 7 Jeumpa, Southwest Aceh District do not have high motivation in achieving their dreams and also that some of these students are still hesitant in determining their dreams, so they only follow what is conveyed by other students. That way, the results of this service provide a clear picture of the dream they will achieve and good motivation for students to pursue that dream.